Examining the Effect of Partial and Complete Elimination of a Specific Disease on the Gain in Life Expectancy at Birth in India and Selected States - Bal Kishan Gulati; Damodar Sahu; Saurabh Sharma; Vishnu Vardhana Rao M (Shahid Sadoughi University of Medical Sciences, 2023)
Background:  Life expectancy, especially life expectancy at birth is a good indicator of current health condition of the population and is estimated through life tables. The present study aims to examine the effect of partial and complete elimination of a specific disease on the gain in life expectancy at birth by sex in India and selected states using Medical Certification of Cause of Death (MCCD) secondary data for 2017. Methods:  Life tables were constructed for all cause-specific deaths using Greville method for both males and females separately for India and selected states.  Cause-deleted life tables were also constructed for partial (25%, 50%, 75%) and complete (100%) elimination of ten leading cause of death groups.  Gain in life expectancy was estimated as the difference between values of cause-deleted life tables and cause-specific life tables. Results: Complete elimination of diseases of the circulatory system yielded maximum gain in life expectancy at birth in males (14.64 years) and in females (15.49 years) both in Haryana. It was followed by diseases of the respiratory system in males (6.45 years) in Jharkhand and in females (6.17 years) in Uttar Pradesh; certain infectious and parasitic diseases in males (3.82 years) in Uttar Pradesh and in females (3.58 years) in Delhi; neoplasms in males (2.71 years) and in females (2.11 years) both in Kerala.  Similar results were obtained in case of remaining diseases. Conclusions:  Maximum gained years would be obtained after reducing mortality from diseases of the circulatory system.  These may have implications for practical decision making in setting up health goals, allocating resources, and launching tailor-made health care programs.